Sharing of Prey: Coinfection of a Bacterium by a Virus and a Prokaryotic Predator - Huan Chen (American Society for Microbiology, 2012)
ABSTRACT Rarely, if ever, has a single bacterial cell been confirmed to simultaneously host two fundamentally different predators. Two such predators are viruses and the predatory prokaryotes known as Bdellovibrio and like organisms. Viruses or bacteriophage are particles requiring prey cells in an active metabolic state to complete their life cycle. The Bdellovibrio and like organisms, unlike viruses, are bacteria that can efficiently infect and grow in prey which are in stationary phase. In this study, electron microscopic examination revealed an unprecedented coinfection by the two agents of Vibrio vulnificus, introducing a new bacterial predation paradigm. Rather than the viruses and Bdellovibrio and like organisms competing for a single prey cell, both can survive in the same cell and successfully reproduce themselves. This is an especially valuable mechanism when the prey is in short supply, and the survival of the predators may be at stake. IMPORTANCE This article describes the coinfection of a prokaryotic prey or host cell by both a bacteriophage (phage) and the predatory bacterium of the group Bdellovibrio and like organisms (BALOs). Such coinfection has not been previously reported and therefore introduces a new paradigm for predation of bacteria. This finding invites new studies on the interactions of BALOs, phage, and prey in predation. Predation is an important mechanism in nature for helping to keep bacterial populations in check and also plays a major role in the cycling of nutrients through the microbial loop. How dual infection by phage and BALOs imposes on these and other functions of predation is fertile ground for future studies and serves as a keystone reference on bacterial predation and mortality.